Efektivitas dan Keamanan Dupilumab pada Remaja dengan Dermatitis Atopik yang Tidak Terkendali: Tinjauan Sistematis: Tinjauan Sistematis - Andrianus, Kenny; Agustin, Triana; Hapsari, Windy Atika (Cermin Dunia Kedokteran, 2026)
Introduction: Up to 24.6% of young adults worldwide suffer from atopic dermatitis. Dupilumab was originally intended for adults with uncontrolled moderate to severe atopic dermatitis. As of March 2019, it has been approved by the US Food and Drug Administration (FDA) for use in adolescents aged 12 to 17. This article aims to evaluate the efficacy and safety of dupilumab in adolescents with uncontrolled moderate to severe atopic dermatitis compared to standard therapy. Methods: A literature search was conducted in June 2020 across Cochrane, EBSCO, and PubMed using specific medical subject heading (MeSH) terms. Inclusion and exclusion criteria were applied. Only relevant articles were selected and appraised using the Center for Evidence-based Medicine (CEBM) tools. Results: Two articles were selected: 1 RCT and 1 cohort study, with 251 and 40 subjects, respectively. Both studies showed statistically significant reductions across all parameters evaluated with Investigator Global Assessment (IGA), Eczema Area and Severity Index (EASI), and Pruritus Numerical Rating Scales. The effectiveness of dupilumab is positively correlated with dosage, frequency, and treatment duration. In both studies, the 4 mg per kg body weight group compared to the 2 mg per kg body weight group, and the every 2 weeks’ protocol compared to the every 4 weeks’ protocol showed better effectiveness. The most common side effects include conjunctivitis, skin infections, and local reactions due to injections. Conclusion: Dupilumab is effective for treating uncontrolled atopic dermatitis in adolescents. The IGA, EASI, and pruritus NRS parameters showed significant reductions. Side effects associated with dupilumab are minimal and well-tolerated.